2008
DOI: 10.4315/0362-028x-71.10.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Kinetics of Three Listeria monocytogenes Strains under High Hydrostatic Pressure

Abstract: High hydrostatic pressure (HHP) inactivation of three Listeria monocytogenes strains (EGDe, LO28, and Scott A) subjected to 350 MPa at 20 degrees C in ACES buffer resulted in survival curves with significant tailing for all three strains. A biphasic linear model could be fitted to the inactivation data, indicating the presence of an HHP-sensitive and an HHP-resistant fraction, which both showed inactivation according to first-order kinetics. Inactivation parameters of these subpopulations of the three strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…Previous research showed that heterogeneity in L. monocytogenes populations (strains EGDe, LO28, and Scott A) affects resistance to high hydrostatic pressure (HHP). Inactivation of such heterogeneous populations resulted in survival curves with significant tailing, indicating the presence of an HHP-sensitive and an HHP-resistant fraction (32). Analysis of the cells that survived such HHP treatments revealed that the higher resistance of LO28 (32) and Scott A (17, 18) was a stable feature for part of the resistant fraction.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research showed that heterogeneity in L. monocytogenes populations (strains EGDe, LO28, and Scott A) affects resistance to high hydrostatic pressure (HHP). Inactivation of such heterogeneous populations resulted in survival curves with significant tailing, indicating the presence of an HHP-sensitive and an HHP-resistant fraction (32). Analysis of the cells that survived such HHP treatments revealed that the higher resistance of LO28 (32) and Scott A (17, 18) was a stable feature for part of the resistant fraction.…”
mentioning
confidence: 99%
“…Inactivation of such heterogeneous populations resulted in survival curves with significant tailing, indicating the presence of an HHP-sensitive and an HHP-resistant fraction (32). Analysis of the cells that survived such HHP treatments revealed that the higher resistance of LO28 (32) and Scott A (17, 18) was a stable feature for part of the resistant fraction. Contrary to these results, no stable HHP-resistant isolates were obtained for EGDe (32).…”
mentioning
confidence: 99%
See 3 more Smart Citations